CRISPR-Mediated Activation of αV Integrin Subtypes Promotes Neuronal Differentiation of Neuroblastoma Neuro2a Cells - Riccardi, Sara; Cingolani, Lorenzo A.; Jaudon, Fanny (Frontiers in Genome Editing, 2022)
Neuronal differentiation is a complex process whose dysfunction can lead to brain disorders. The development of new tools to target specific steps in the neuronal differentiation process is of paramount importance for a better understanding of the molecular mechanisms involved, and ultimately for developing effective therapeutic strategies for neurodevelopmental disorders. Through their interactions with extracellular matrix proteins, the cell adhesion molecules of the integrin family play essential roles in the formation of functional neuronal circuits by regulating cell migration, neurite outgrowth, dendritic spine formation and synaptic plasticity. However, how different integrin receptors contribute to the successive phases of neuronal differentiation remains to be elucidated. Here, we implemented a CRISPR activation system to enhance the endogenous expression of specific integrin subunits in an in vitro model of neuronal differentiation, the murine neuroblastoma Neuro2a cell line. By combining CRISPR activation with morphological and RT-qPCR analyses, we show that integrins of the αV family are powerful inducers of neuronal differentiation. Further, we identify a subtype-specific role for αV integrins in controlling neurite outgrowth. While αVβ3 integrin initiates neuronal differentiation of Neuro2a cells under proliferative conditions, αVβ5 integrin appears responsible for promoting a complex arborization in cells already committed to differentiation. Interestingly, primary neurons exhibit a complementary expression pattern for β3 and β5 integrin subunits during development. Our findings reveal the existence of a developmental switch between αV integrin subtypes during differentiation and suggest that a timely controlled modulation of the expression of αV integrins by CRISPRa provides a means to promote neuronal differentiation.